2007
DOI: 10.3136/fstr.13.270
|View full text |Cite
|
Sign up to set email alerts
|

Bitter-Tasting Sake Peptides Derived from the N-Terminus of the Rice Glutelin Acidic Subunit

Abstract: Five bitter-tasting peptides were isolated from charcoal-untreated sake, following a Sepabeads resin separation, an initial reverse-phase chromatography (RP-HPLC), a gel permeation-chromatography, and a second RP-HPLC. The isolated peptides consisted of six to thirteen amino acid residues. The N-termini were uniformly pyroglutamate residues. Based on the rice protein database, the peptides were derived from two di#erent N-termini of the rice glutelin acidic subunit. One of them was reported as a prolyl endopep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…A large number of the peptides identified in this experiment presented a higher hydrophobicity (Bull+Breese value, data not shown) that is closely related to the bitterness of peptides 23 , which indicates that they may exhibit a potential bitter taste. However, the five bitter-taste peptides reported by Hashizume et al 10 were not found in this experiment, possibly because the Chinese rice wine (Huang Jiu) was produced using significantly different materials, microorganisms and wine-making technology or for other unknown reasons compared with sake. However, the ACE-active peptides, VY and YW, were found in this experiment as also reported by Saito et al 31 who had screened for them and found them in sake and sake lees.…”
Section: Potential Activity Of the Peptidescontrasting
confidence: 41%
See 2 more Smart Citations
“…A large number of the peptides identified in this experiment presented a higher hydrophobicity (Bull+Breese value, data not shown) that is closely related to the bitterness of peptides 23 , which indicates that they may exhibit a potential bitter taste. However, the five bitter-taste peptides reported by Hashizume et al 10 were not found in this experiment, possibly because the Chinese rice wine (Huang Jiu) was produced using significantly different materials, microorganisms and wine-making technology or for other unknown reasons compared with sake. However, the ACE-active peptides, VY and YW, were found in this experiment as also reported by Saito et al 31 who had screened for them and found them in sake and sake lees.…”
Section: Potential Activity Of the Peptidescontrasting
confidence: 41%
“…Hofmann's research group has found many key bitter and kokumi peptides in Gouda cheeses and edible beans 7,34,35 . Hashizume et al 10 reported that five peptides isolated from sake presented the unpleasant taste with an accompanying bitter taste.…”
Section: Identification Of Low Molecular Weight Peptides In Chinese Rmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of peptides derived from proteins have been found in various foodstuffs and fermentation products, such as miso (salted and fermented soybean paste) [18], soy sauce [19,20], fish sauce [21], natto (fermented soybeans) [22], katsuobushi (dried fish flakes) [23], cheese [24 -27], and sake [28,29]. Hydrolysis of proteins by proteolytic enzymes is also usually accompanied by the formation of a bitter taste [30 -33].…”
Section: Bitter Peptides In Protein Hydrolysatesmentioning
confidence: 99%
“…Especially, a low protein content is an important feature for high-quality sake brewing, because an excess amount of proteins (amino acids) causes a rough taste and deepening of the color of the refined sake, which are negative factors in terms of sensory evaluation. [1][2][3] Furthermore, the aroma of sake containing a high content of amino acids appears to deteriorate during storage. 1) As the germ and the surface fraction of the rice grain are abundant in proteins and lipids, the rice used for high-quality sake brewing is highly polished to reduce these negative factors for sake taste.…”
mentioning
confidence: 99%